Y=3x(2x-1)(x+3)

Simple and best practice solution for Y=3x(2x-1)(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y=3x(2x-1)(x+3) equation:


Simplifying
Y = 3x(2x + -1)(x + 3)

Reorder the terms:
Y = 3x(-1 + 2x)(x + 3)

Reorder the terms:
Y = 3x(-1 + 2x)(3 + x)

Multiply (-1 + 2x) * (3 + x)
Y = 3x(-1(3 + x) + 2x * (3 + x))
Y = 3x((3 * -1 + x * -1) + 2x * (3 + x))
Y = 3x((-3 + -1x) + 2x * (3 + x))
Y = 3x(-3 + -1x + (3 * 2x + x * 2x))
Y = 3x(-3 + -1x + (6x + 2x2))

Combine like terms: -1x + 6x = 5x
Y = 3x(-3 + 5x + 2x2)
Y = (-3 * 3x + 5x * 3x + 2x2 * 3x)
Y = (-9x + 15x2 + 6x3)

Solving
Y = -9x + 15x2 + 6x3

Solving for variable 'Y'.

Move all terms containing Y to the left, all other terms to the right.

Simplifying
Y = -9x + 15x2 + 6x3

See similar equations:

| .10(x+7)=30 | | 18=2g | | .25v-.42=.28v-.25 | | -4(x-3)-13=3(x+2) | | V=(10-2x)(8-2x) | | c(3)=15 | | 2x^2=13x+24 | | 6+2x=-6x-90 | | 5x-10+1x+3=8 | | 13+5r=2(5+2r) | | 4(7x+4)-9=28x+7 | | x^3+5x+3x+15=0 | | 4a+2=3a+7 | | 0=-4x^2-16x+20 | | 201(6+6)= | | 2-4h=6-6h | | -50+1.0x=300 | | 4x-3=-103-6x | | Y=-4x-16x+20 | | 2x+5-8w=7-4w | | 3m+3-m=3(m+1) | | -1v+5+4v=1+5v+3 | | (2i+3)(7i+6)= | | 9x+6(3x-4)=12-9x | | 3a-11=4(a+1)+13a+3 | | 2g-8+3g=7 | | .17(x+29)=86 | | 2x-6=5x+27 | | 2y^2-7y-10=0 | | 4x-2(.50-1)=14 | | 101(87+13)= | | y^3+729= |

Equations solver categories